Unilateral spatial neglect in the acute phase of ischemic stroke can predict long-term disability and functional capacity - Luvizutto, Gustavo José; Moliga, Augusta Fabiana [UNESP]; Rizzatti, Gabriela Rizzo Soares [UNESP]; Fogaroli, Marcelo Ortolani [UNESP]; de Moura Neto, Eduardo; de Carvalho Nunes, Hélio Rubens [UNESP]; de Lima Resende, Luiz Antônio [UNESP]; Bazan, Rodrigo [UNESP] (Elsevier, 2018)
OBJECTIVE: The aim of this study was to assess the relationship between the degree of unilateral spatial neglect during the acute phase of stroke and long-term functional independence. METHODS: This was a prospective study of right ischemic stroke patients in which the independent variable was the degree of spatial neglect and the outcome that was measured was functional independence. The potential confounding factors included sex, age, stroke severity, topography of the lesion, risk factors, glycemia and the treatment received. Unilateral spatial neglect was measured using the line cancellation test, the star cancellation test and the line bisection test within 48 hours of the onset of symptoms. Functional independence was measured using the modified Rankin and Barthel scales at 90 days after discharge. The relationship between unilateral spatial neglect and functional independence was analyzed using multiple logistic regression that was corrected for confounding factors. RESULTS: We studied 60 patients with a median age of 68 (34-89) years, 52% of whom were male and 74% of whom were Caucasian. The risk for moderate to severe disability increased with increasing star cancellation test scores (OR=1.14 [1.03-1.26], p=0.01) corrected for the stroke severity, which was a confounding factor that had a statistically positive association with disability (OR=1.63 [1.13-2.65], p=0.01). The best chance of functional independence decreased with increasing star cancellation test scores (OR=0.86 [0.78-0.96], p=0.006) corrected for the stroke severity, which was a confounding factor that had a statistically negative association with independence (OR=0.66 [0.48-0.92], p=0.017). CONCLUSION: The severity of unilateral spatial neglect in acute stroke worsens the degree of long-term disability and functional independence.
Keywords: Autonomy; Functional independence; Incapacity; Stroke; Unilateral spatial neglect